1996
DOI: 10.1109/69.506716
|View full text |Cite
|
Sign up to set email alerts
|

Towards the correctness and consistency of update semantics in semantic database schema

Abstract: This paper discusses a paradigm and prototype system for the design-time expression, checking, and automatic implementation of the semantics of database updates. Here, enforcement rules are viewed as the implementation of constraints and are specified, checked for consistency, and then finally mapped to object-oriented code during database design. A classification of enforcement rule types is provided as a basis for these design activities, and the general strategy for specification, analysis, and implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Elmasri & Larson, 1985;Markowits & Shoshani, 1989;Anderson & Shin, 1991;Chang & Sciore, 1992;Chan et al, 1993;Siau et al, 1995;Peckham, Maryanski & Demurjian, 1996;Bloesch & Halpin, 1997). The more recent prototypical approaches in Chang and Sciore (1992), Peckhan et al (1996), Siau et al (1995) and Chan et al (1993) elevate query formulation from the logical level to the conceptual schema level by supporting the direct use of concepts and abstractions on conceptual schema in query statements.…”
Section: Motivationmentioning
confidence: 91%
“…Elmasri & Larson, 1985;Markowits & Shoshani, 1989;Anderson & Shin, 1991;Chang & Sciore, 1992;Chan et al, 1993;Siau et al, 1995;Peckham, Maryanski & Demurjian, 1996;Bloesch & Halpin, 1997). The more recent prototypical approaches in Chang and Sciore (1992), Peckhan et al (1996), Siau et al (1995) and Chan et al (1993) elevate query formulation from the logical level to the conceptual schema level by supporting the direct use of concepts and abstractions on conceptual schema in query statements.…”
Section: Motivationmentioning
confidence: 91%
“…To attack this problem, SQL3 (Markowitz, 1991) restricts the order of operations. For the similar anomalies in OODBMS environment, Peckham et al (1996) suggested a solution which notifies the possible anomalies to users when a schema may cause problems.…”
Section: Destructor and Assignment Operatormentioning
confidence: 99%
“…Integrating databases [8,20,24] • Resolve semantic heterogeneity • Present a model that allows for uniform specification of database requests and for an application program Integrating semantics into databases [23,32] • Automatically implement the semantics of database updates • Support the semantics and the object-oriented modeling of software environments Architecture of data warehouses [6,7,25] • Define the architecture of data warehouses • Use O-O technology to consider the model of data warehouses • Discuss access methods in data warehouse systems Object-oriented analysis [2,17,19,26] • Define a core conceptual OO database model • OO design with application • OO modeling and design • OO software engineering Data cube operations [10,12,13,16,21,28,30] • Use greedy algorithms to implement an optimal data cube model • Use greedy algorithms to automate the selection of summary tables and indexes • Propose a greedy method to select material views and, in turn, to recompute the size of the stored views • Use SQL statements to implement data cubes and to provide several functions of data cube operations in data warehouses Applications of data warehouse systems [4,27,34] • Implement effective commerce-strategy analyses of data warehouse projects • Develop applications to integrate the data warehouses and DSS into the real environment • Apply a multi-agent approach to brain modeling and neurofuzzy control in the data warehouse environment…”
Section: Relevant Research Featuresmentioning
confidence: 99%